2017
DOI: 10.1111/oik.03869
|View full text |Cite
|
Sign up to set email alerts
|

Functional flower traits and their diversity drive pollinator visitation

Abstract: Recent studies have shown that the diversity of flowering plants can enhance pollinator richness and visitation frequency and thereby increase the resilience of pollination. It is assumed that flower traits explain these effects, but it is still unclear which flower traits are responsible, and knowing that, if pollinator richness and visitation frequency are more driven by mass-ratio effects (mean trait values) or by trait diversity.Here, we analyse a three-year data set of pollinator observations collected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 60 publications
7
85
2
Order By: Relevance
“…Here, we found that trait matching between plants and animals was the main driver of the functional trait composition of avian frugivore communities on Mount Kilimanjaro. Consistent with our results, specific traits of flowering plants affected the species richness and visitation frequency of animal pollinators in a small‐scale, experimental system (Fornoff et al, ). Hence, bottom‐up effects mediated by plant traits and biotic interactions appear to be an important mechanism influencing patterns of animal diversity across spatial scales.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we found that trait matching between plants and animals was the main driver of the functional trait composition of avian frugivore communities on Mount Kilimanjaro. Consistent with our results, specific traits of flowering plants affected the species richness and visitation frequency of animal pollinators in a small‐scale, experimental system (Fornoff et al, ). Hence, bottom‐up effects mediated by plant traits and biotic interactions appear to be an important mechanism influencing patterns of animal diversity across spatial scales.…”
Section: Discussionsupporting
confidence: 91%
“…Measurements were collected every week, alternating between Helena and Paradise, throughout the growing season to allow for measurements during peak flowering for each species. Plant height was measured from the ground to the top of the inflorescence of a flowering individual, and can be important for plant reproduction as taller plants are more visible and often attract more pollinators (e.g., Fornoff et al, 2017). The number of flowers was counted on a randomly selected inflorescence, and is a measure of plant attractiveness to pollinators (Conner and Rush, 1996;Coux et al, 2016).…”
Section: Functional Traits Of Flowering Plantsmentioning
confidence: 99%
“…Leaf rachis and petiolules (for species with compound leaves) and petioles (for all species) were included in measurements of leaf area and dry mass. SLA is important for plant energy use and potential relative growth rate (Cornelissen et al, 2003;Vieira et al, 2013;Fornoff et al, 2017). Though SLA may not be important for pollinator attraction or rewards, we included this commonly-measured trait to gain information on the plant perspective of the potential effects of wildfire and how these effects may differ from those on plant traits important for bees.…”
Section: Functional Traits Of Flowering Plantsmentioning
confidence: 99%
“…The species richness and abundance of bumblebees are significantly affected by types of flower resources, indicating that there is a strong association of bumblebees with families of host plants across the study area. Many explanations have pointed out how flora characters such as morphology, color and scent are associated with the attraction of the bee communities (Stone et al, 2003, Cnaani et al, 2006Fornoff et al, 2017). Elliott (2009) resulted the relation of foraging distances, bumblebee and flower availability (Williams and Osborne, 2009) indicated that species richness of bumblebee depends on increasing flower cover and the type of host plant and their richness compared to the other factors.…”
Section: Discussionmentioning
confidence: 99%